Asociación entre altura, diámetro y amplitud de copa en plantas de calycophyllum spruceanum “capirona” en una plantación, Puerto Almendra, Loreto, Perú, 2021 - Casanova Arias, Brilli Franchesca (2024)
The general objective of the study was to determine the association between the variables diameter & total height; diameter & crown width and crown width & total height in the growth of Calycophyllum spruceanum “capirona” plants in a CIEFOR Puerto Almendra plantation, Loreto, Peru. The variables evaluated were the diameter, total height and crown width of the plants of the species under study; The data were obtained from the representative sample of 44 individuals. The results show that in the associations evaluated there is no difference in the allometric model that best fits these associations, which was the cubic one, but they were different in the degree of association between them, in diameter & total height it was excellent; in diameter & crown width it was good and in crown width & total height it was average; Regarding the affinity between the variables, it was as follows: 76%, 27% and 23% respectively.